Sustainability Metrics in Software Development Practices in India - Sharma, Aditi (American Journal of Computing and Engineering, 2024)
Purpose: The aim of the study was to assess the sustainability metrics in software development practices in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This study highlighted the integration of green coding practices, which focus on optimizing code to reduce energy usage and prolong the lifespan of hardware components. Additionally, lifecycle assessments are utilized to evaluate the long-term environmental effects of software products, from development through to disposal. Social sustainability metrics also play a role, addressing factors such as diversity in development teams and ethical considerations in software applications. Innovative approaches like DevOps practices contribute to sustainability by streamlining development processes and reducing resource wastage. Continuous integration and continuous deployment (CI/CD) pipelines are leveraged to automate testing and deployment, enhancing efficiency and reducing unnecessary computational overhead. The adoption of cloud computing is another notable trend, offering scalable resources that can be adjusted according to demand, thus optimizing energy use. Furthermore, sustainable software development often encompasses user-centric design principles that ensure software meets the needs of diverse populations, promoting inclusivity and accessibility. These comprehensive sustainability metrics collectively drive the movement towards more responsible and environmentally conscious software development practices. Implications to Theory, Practice and Policy: Triple bottom line theory, systems thinking theory and resource-based view theory may be used to anchor future studies on assessing the sustainability metrics in software development practices in India. In terms of practical contributions, software development teams should prioritize the implementation of standardized sustainability metrics derived from research findings. On the policy front, it is recommended to advocate for regulatory support that incentivizes and supports sustainable software development practices.